(untitled) (Research, Society and Development, 2021)
In Brazil, and specifically in the South Region, it is discussed how to find alternatives to be able to adjust spending to what was actually planned. In this context, the Fiscal Responsibility Law (LRF) contributes to greater control and accountability of public spending. Thus, the objective of this study is to make an analysis of the municipalities of the three states of the Southern Region of Brazil regarding their evolution in relation to LRF and the revenues and expenses in the period between 2011 and 2018. The research method used to elaborate the The article is descriptive, quantitative and documentary. It is concluded that in the course of the analyzed time, there was a great evolution of the municipalities with the intention of adapting the impositions of the law, however, there is difficulty of the small municipalities in maintaining the balance in the public accounts. Thus, in a broad way, Santa Catarina’s citizens demonstrated that they have great recurrences and difficulties in closing the exercises due to large expenses, and also in terms of limits on personnel expenses, which together with Paraná municipalities represent a high number of noncompliance with the limit. Thus, the state of Rio Grande do Sul presented the best indexes of the study, considering the situation of the municipalities, as well as an evolutionary temporal analysis.